The New Arctic: A Sanctuary or a Globalized Region of Potential - Matthildur María Rafnsdóttir 1997- (2022)
This thesis sheds light on how climate change impacts outside actors’ view of the Arctic. Global warming has put the Arctic into the limelight of international debates because what happens in the Arctic does not stay in the Arctic. Therefore, non-Arctic states and other outside actors have expressed and shown increased interest in the region and wish to have a say in its development. Semi-structured interviews were used in this thesis to give an in-depth dimension to the study and how people living in the Arctic view the region. Content analysis was applied to six Arctic policies of non-Arctic states, neoliberal institutionalism and green theory are used to provide a theoretical framework for the research questions. The main results of the research are that the six non-Arctic states studied view the region as open and full of opportunities for further development. According to the interviews, creating a sanctuary in the Arctic is unlikely to be successful if it comes from an outside actor and if it indicates an exclusionary approach, separating humans from nature.